Moral value in "Osakat Anak Asmat" story written by Ani Sekarningsih (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2022)
The purpose of this study was to study the moral values and character education in the story Osakat Anak Asmat by Ani Sekarningsih which was used as teaching material. The method is descriptive qualitative with an approach of content analysis. The data are written words from a subject that has been observed. The subject of this study is the story. Data analysis contains the value of character education that is contained in the story. The results showed that: (1) nine characters values were issued by the Ministry of National Education and Culture, namely independence, discipline, social care, curiosity, friendly/communicative, religious, hard work, creativity, and rewarding achievement; (2) four moral characters can be emulated, namely obedience to parents, sharing or giving, patience, and wise; and (3) three behaviors are not exemplary, namely irresponsible, discouraging friends and jealousy.